Comparison of the home advantage in nine different professional team sports in spain - Gomez, M. A.; Pollard, R.; Luis-Pascual, J. C. (Perceptual and Motor Skills, 2011)
Home advantage is a well-established phenomenon in many sports. The present study is unique in that it includes different sports analysed in the same country, at the same level of competition, and over the same time period. Nine team sports from Spain were included: baseball, basketball, handball, indoor soccer, roller hockey, rugby, soccer, volleyball, and water polo. Data for five seasons (2005-2006 to 2009-2010) were obtained, totaling 9,472 games. The results confirmed the existence of home advantage in all nine sports. There was a statistically significant difference between the sports; home advantage was highest in rugby (67.0%), and lowest in volleyball (55.7%), water polo (56.2%), and roller hockey (58.3%). The design of the study controlled for some of the likely causes of home advantage, and the results suggested that the high home advantage for rugby was likely a reflection of the continuous, aggressive, and intense nature of the sport.